Pendekatan Travel Cost Method (TCM) Dalam Pengukuran Nilai Ekonomi Kawasan Agrowisata Tuur Ma’asering Di Desa Kumelembuai Kecamatan Tomohon Timur Kota Tomohon - Arie, Mona Cintya; Mandei, Juliana Ruth; Waney, Nordy Fritsgerald Lucky (Sam Ratulangi University, 2024)
This study aims to estimate the economic value of Agrowisata Tuur Ma’asering using the Travel Cost Method (TCM) approach and to analyze the factors affecting the demand for visits to Agrowisata Tuur Ma’asering. The research was conducted over 3 months, from February to May 2024. Data collection was performed using a survey method, gathering both primary and secondary data. Sampling was done using accidental sampling techniques, with the sample size determined by a linear time function formula, resulting in 58 respondents. The research method employed is quantitative, utilizing the travel cost method (TCM) and multiple linear regression analysis. The results indicate that the economic value of Agrowisata Tuur Ma’asering, calculated using the Travel Cost Method (TCM), is IDR2,027,876,535. This value is derived from the consumer surplus per individual per month of IDR345,759, multiplied by the number of visitors in April 2024, which is 5,865 visitors. Factors influencing the demand for visits to Agrowisata Tuur Ma’asering include travel costs, income, education level, and group size. Factors that do not have a significant impact are travel distance and age.